2016
DOI: 10.4103/1319-2442.194889
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis delivery, dialysis dose achievement, and vascular access types in hemodialysis patients from the Gulf Cooperation Council countries enrolled in the dialysis outcomes and practice patterns study phase 5 (2012-2015)

Abstract: The prospective observational Dialysis Outcomes and Practice Patterns Study (DOPPS) was initiated in late 2012 in national samples of hemodialysis (HD) units (n = 41 study sites) in all six Gulf Cooperation Council (GCC) countries (Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, and the United Arab Emirates). For many years, guidelines have recommended single pool Kt/V ≥1.2 as the minimum adequate dose for chronic HD patients. Here, we report initial DOPPS results regarding HD practices related to dialysis dose ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 1 publication
2
10
0
Order By: Relevance
“…Additionally, under flow conditions, the rougher membrane leads to a clear increase in the release of C5b-9 and vWF, which confirms the mechanical hemolysis due to the increased shear stress experienced near the membrane surface 44 .A rougher surface intensifies FB adsorption, which leads to more severe inflammatory response in HD patients 41 , 42 . Importantly, the Qb range investigated is on the lower side of the spectrum of prescribed Qb for Canadian and American patients (mean prescribed Qb of 371.85 and 425.42 mL/min 45 , respectively), so a more pronounced tendency for hemolysis can be expected for those patients, especially when rough membranes are used.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, under flow conditions, the rougher membrane leads to a clear increase in the release of C5b-9 and vWF, which confirms the mechanical hemolysis due to the increased shear stress experienced near the membrane surface 44 .A rougher surface intensifies FB adsorption, which leads to more severe inflammatory response in HD patients 41 , 42 . Importantly, the Qb range investigated is on the lower side of the spectrum of prescribed Qb for Canadian and American patients (mean prescribed Qb of 371.85 and 425.42 mL/min 45 , respectively), so a more pronounced tendency for hemolysis can be expected for those patients, especially when rough membranes are used.…”
Section: Discussionmentioning
confidence: 99%
“…The study results fall in the range of CVC usage in Gulf countries ranging from 29% in Oman to 56% in Kuwait, which is considered high according to the international guidelines. 12 Despite clear international guidelines for timely initiation of a HD via AVF, the rates remain poor. Several factors attribute to this internationally, both remedial and non-remedial.…”
Section: Resultsmentioning
confidence: 99%
“…Most dialysis catheters can be capable of achieving flow rates exceeding 300 mL/min, with the intent of producing a more efficient dialysis session. However, recent studies showed that countries that had high success in hemodialysis had a much lower average blood flow rate (200mL/min) (Pisoni et al , Alyousef et al 2016. In Europe and in Saudi Arabia, for example, a blood flow rate lower than 300 mL/min is frequently used in dialysis treatment, once the adequate hemodialysis depends on certain factors that include duration and frequency of dialysis sessions, dialyzer size, dialysate characteristics, blood flow rate, vascular access, protein intake, physical activity, and hematocrit (Alyousef et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, flow rate values within the CVC may vary during the hemodialysis sessions and the professionals do not take into account the difference in flow rate values and the increased possibility of thrombus formation. Early identification of the presence of the thrombus by means of flow rate variation may contribute to reduce morbidity and to the maintenance of venous access, especially for End Stage Renal Disease (ESRD) patients with limited vascular access (Alyousef et al 2016). Figure 4 and Table I show that by the power regression model the exponent presented small variations when compared to the different catheter sizes.…”
Section: Discussionmentioning
confidence: 99%